2020
DOI: 10.1371/journal.pone.0233137
|View full text |Cite
|
Sign up to set email alerts
|

Personal and psychosocial factors of burnout: A survey within the French neurosurgical community

Abstract: The neurosurgical community is particularly exposed to burnout. The objectives of this study were to report the prevalence and associated factors of burnout within the French neurosurgical community using validated academic and psychologic scales. MethodsA national survey was sent to 141 French residents and 432 neurosurgeons between April and July 2019. Burnout was surveyed using the Maslach burnout inventory. The survey included demographic data and several academic psychologic scales. A stepwise multiple re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 48 publications
2
18
0
3
Order By: Relevance
“…This leads to the assumption that enjoyment, in particular, could be the driving force explaining the protective effect of flow experience on burnout symptoms. This is in line with the interpretation suggested by Baumgarten et al [ 80 ], namely that enjoyment during working hours should be seen as a protective factor against emotional exhaustion and feelings of cynicism. The importance of enjoyment could stem from the fact that, as a positive emotion, it helps to better relieve stressful situations and to show the positive meaning in these situations [ 118 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This leads to the assumption that enjoyment, in particular, could be the driving force explaining the protective effect of flow experience on burnout symptoms. This is in line with the interpretation suggested by Baumgarten et al [ 80 ], namely that enjoyment during working hours should be seen as a protective factor against emotional exhaustion and feelings of cynicism. The importance of enjoyment could stem from the fact that, as a positive emotion, it helps to better relieve stressful situations and to show the positive meaning in these situations [ 118 ].…”
Section: Discussionsupporting
confidence: 92%
“…This finding substantiates the hypothesis that flow experience has an addictive potential [ 60 ] that may eventually result in increased exhaustion. Such reasoning is further supported by the positive correlations between excessive working and exhaustion [ 80 ] on the one hand and excessive working and absorption [ 119 ] on the other. This permits the assumption that absorption leads to symptoms of emotional exhaustion via workaholism.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Several traits have been shown to be protective against burnout. 4,5 However, rather than attempting to select for those traits, training programs should aim to create an environment that fosters wellness and career satisfaction. Although neurosurgery trainees experiencing burnout frequently state that they would choose neurosurgery again, 66% state that they would elect to train at another program.…”
Section: Responsementioning
confidence: 99%
“…1 New contemporary concerns are the mismatch between the growing number of students in the neurosurgery programs and the low number of fellowships available (which induces stressful uncertainty for the residents' future early career), 3 the limited access to neurosurgical literature and publication opportunities, and the fearful atmosphere caused by the recent judicialization of neurosurgical practice, which can lead to defensive attitudes and even professional disenchantment. 4 Beyond these considerations, Baumgarten et al showed that specific personality traits such as openness, agreeableness, and conscientiousness were protective, whereas neuroticism was negatively associated with burnout. They also showed that pleasure at work was protective.…”
mentioning
confidence: 99%